Synergistic enhancement of strength and ductility of cobalt-free maraging steel via nanometer-scaled microstructures - Li, Hu; Liu, Yong; Liu, Bin; Wei, Daixiu (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2022)
Maraging steel with ultra-high strength and good ductility is usually achieved via semi-coherent nanometer-sized precipitates and a dual-phase structure. In this work, we studied the effect of solution treatment parameters on the microstructural evolution and the mechanical properties of cobalt-free maraging steel, with high strength (1852 MPa) and satisfactory tensile elongation (11.5%) at room temperature was obtained. The nano-scaled precipitates in the martensite matrix were analyzed, in which the η-Ni3(Ti, Mo) precipitates were distributed in width of 7.1 nm and length of 19 nm. It was found that the needle-like Ni3Ti phase plays a predominant role in enhancing the strength of the maraging steel, while the ductility can be attributed to the nano laminated austenite structure, which could effectively prevent the propagation of microcracks in the martensite matrix. A heterogeneous microstructure of precipitates was formed in the martensite matrix. Besides, the size and number density of precipitates could be regulated by tuning the solution treatment conditions, in which a finer size and a larger number of precipitates could be gained by annealing at a high temperature for a short time.